Study of factors associated with silent myocardial ischemia in hypertensive diabetic patients followed-up in the cardiology department of Yalgado Ouédraogo Teaching Hospital - KOLOGO, Koudougou Jonas; TALL-THIAM, Anna; KABORE-BENON, Laurence Eudoxie; MILLOGO, Geoges Rosario Christian; KAMBIRE, Yibar; KAGAMBEGA, Larissa Justine; KABORE, Elisé Guetawendé; SOME, Martin Zoubadar; TRAORE, Sékou; NABI, Koulibi Julien; KOLOGO, Wendkonta Reine Lydie Flora; NEBIE, Lucie Valérie Adélaide; et al. (Journal of Cardiology and Cardiovascular Medicine, 2025)
Objective: Study the association between anti-ischemic chemoprophylaxis (ACE inhibitor, statin, and antiplatelet agent) and the reduced risk of the occurrence of silent myocardial ischemia in hypertensive diabetic subjects. Methodology: This was an observational, retrospective, prospective case-control study conducted from January 1 to November 30, 2018. It involved 94 patients distributed into 47 cases and 47 controls following the result of the exercise stress test performed in the cardiology department of Yalgado Ouédraogo Teaching Hospital in Ouagadougou, Burkina Faso. Results: The average age of the cases was 55.98 ± 8.6 years against 56.11 ± 7.57 years for the controls; the sex ratio was in favor of women in both groups. Anti-ischemic chemoprophylaxis was found in 25% of cases and 15% of controls. The assessment of the cardiovascular risk showed a high cardiovascular risk level in 34% of cases, against to 35% of controls; an intermediate risk level in 34% of cases, against 41% in controls. Risk factors such as age, dyslipidemia, smoking, and hyperuricemia were not associated with silent myocardial ischemia. Multivariate analysis revealed an association (odds ratio = 0.29; p = 0.048) between chemoprophylaxis and reduction of 71% of the risk of silent myocardial ischemia. Conclusion: Our work highlights the importance of pharmacological treatment of hypertensive diabetic patients as a primary cardiovascular prevention.